Wewenang Kankain Karkara Byak dalam Menyelesaikan Delik Adat - Deki Demianus Korwa (Kyadiren, 2022)
This study seeks to examine the implementation of the role of Byak’s customary institutions in customary law communities and the effectiveness of customary institutions in carrying out their functions. This type of research was normative-empirical legal research. The results of the study explain that several crimes that have been handled by the Byak’s Kankain Karkara Institution are murder, domestic violence (KDRT), humiliation, Out-of-wedlock births and other crimes that often occur. The obstacle faced by tribal chiefs or mananwir in handling cases is the postponement of the trial due to the perpetrators needing time to pay back loss. In addition, weak evidence makes it difficult to examine. There are some people who solve these problems amicably because they do not want the problems to be known by many people.